The Dynamics of Performance Culture in the Holi Festival: A Critical Analysis - Joshi, Bhup Raj (Journal of Durgalaxmi, 2025)
The Holi festival, primarily celebrated within Hindu society, manifests as a vibrant realm of performance that dissolves social hierarchies and boundaries through communal participation and collective joy. Grounded in performance theory, this paper interprets Holi as a dynamic cultural event that embodies the ideas of Mikhail Bakhtin, Jacques Derrida, Peggy Phelan, and Clifford Geertz. Drawing on Geertz’s notion of “blurred genres,” the study situates Holi at the intersection of ritual, art, and social performance—where the aesthetic, the sacred, and the everyday intertwine. Contrary to critiques that associate the festival with harassment or environmental disruption, this research argues that Holi’s enduring value lies in its capacity to create a liminal space where established norms are momentarily suspended. Through an analysis of mythic narratives and performative practices, Holi emerges as a living, evolving artistic phenomenon that bridges tradition and modernity. As a “Festival of Colors,” it becomes a powerful performance site expressing happiness, transgression, and transformation. The article engages with Mary M. Anderson’s The Festivals of Nepal, Bakhtin’s concept of the carnival, Derrida’s theory of hauntology, Phelan’s ontology of performance, and Geertz’s interpretive anthropology to reveal how Holi blurs the boundaries between sacred and profane, individual and collective, and past and present—transforming cultural ritual into a performative dialogue of identity and renewal.